Co‐Catalyzed Intramolecular S‐N Bond Formation in Water for 1, 2‐Benzisothiazol‐3(2H)‐ones and 1, 2, 4‐Thiadiazoles Synthesis. Issue 6 (7th January 2019) - Yang, Liting; Song, Lijuan; Tang, Shanyu; Li, Longjia; Li, Heng; Yuan, Bingxin; Yang, Guanyu
Abstract : An efficient and versatile Co‐catalyzed intramolecular S‐N bond formation in water to synthesize 1, 2‐benzisothiazol‐3( 2H )‐one and 1, 2, 4‐thiadiazoles derivatives in good to excellent yields was developed. The transformation showed great tolerance with a broad range of substituents. The mother liquor was able to be recycled 6 times with minor loss in product yield. Abstract : Sustainable synthesis of 1, 2‐benzisothiazol‐3( 2H )‐ones and 1, 2, 4‐thiadiazoles via intramolecular S‐N bond formation were realized in aqueous media with good to excellent yields, which used tetra‐sulfonated cobalt phthalocyanine as a catalyst and molecular oxygen as the environment friendly oxidant.